Memoria y violencia : un recorrido por algunas reflexiones y perspectivas (2017)
The article is a product of the revision of the debate on historical memory and violence. Its objective is to trace a way to diagnose the current state of discussions and there flections on this research problem that are being made by diverse authors in different spatial contexts. The document includes a historical contextualization of the studies on memory and violence, the discussions that have generated the approach of recent studies in history, the way in which the memory has been defined from the perspective of some authors, the main sources that have been used in the studies of memory and some approaches that have been done on the relation, memory, violent episodes and construction of subjectivities.